2015
DOI: 10.1111/ijac.12440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of ZnCr2O4 Nanospinel Prepared via Homogeneous Precipitation Using Urea Hydrolysis

Abstract: In situ and homogeneous hydrolysis of urea was utilized to design a homogeneous precipitation method to synthesize the ZnCr2O4 functional material. The as‐prepared nanospinel was systematically studied in terms of crystal structure, morphology, texture, and light absorption. A well‐crystalline single phase of ZnCr2O4 nanospinel with a spongy network structure was obtained. Transmission electron microscopy and X‐ray diffraction observations confirmed the formation of monocrystalline nanoparticles of ZnCr2O4 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…22,23 Of particular interest, the UAHP method has attracted great attention owing to the fairly simple synthesis at mild temperature and ambient pressure, low cost processing and ease scalability. [24][25][26] In addition, this method permits the controlled formation of metal oxide structures from solutionphase precursors such as metal salts in aqueous media and the low-supersaturation conditions derived by slow urea hydrolysis give rise to formation of smaller number of nuclei formed which nally leads to well-crystallized solid material.…”
Section: 13mentioning
confidence: 99%
“…22,23 Of particular interest, the UAHP method has attracted great attention owing to the fairly simple synthesis at mild temperature and ambient pressure, low cost processing and ease scalability. [24][25][26] In addition, this method permits the controlled formation of metal oxide structures from solutionphase precursors such as metal salts in aqueous media and the low-supersaturation conditions derived by slow urea hydrolysis give rise to formation of smaller number of nuclei formed which nally leads to well-crystallized solid material.…”
Section: 13mentioning
confidence: 99%
“…It can be concluded that the nuclei and/or crystallites of Al 2 O 3 could be synthesized during drying; therefore, its related peaks are tiny and wide. The porous structure of the ZnCr 2 O 4 powder is also provided in Figure 4E (This figure has been originally published in the previous work 24 ). Figure 4 shows the FE-SEM images of the dried precipitate (Figure 4A,B) and the calcined powder ( Figure 4C,D) of Al 2 O 3 -ZnCr 2 O 4 .…”
Section: Resultsmentioning
confidence: 98%
“…As can be seen, the thermal behaviors of both samples are similar and the temperature region in which the unique exothermic reaction occurred is 300-500°C. 24 The third pattern is related to the aim of this manuscript namely the Al/Zn/Cr containing solution. However, commenting on this subject needs more characterizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of total pore volume and mean pore diameter is observed with an increase of chromium content. High surface area or low crystallite size of the oxides could be obtained under optimal Cr/Zn ratio and calcination temperature [31,32]. Accordingly, formation of ZnO-Cr-x high surface area materials can be connected with the presence of surface chromium phases, which may hinder fast growth and sintering of ZnO grains during precipitation and thermal treatment.…”
Section: Structural Changesmentioning
confidence: 99%